Los valores del Olimpismo en "El descenso del Sella". La relación del creador Dionisio de la Huerta y el Presidente del C.O.I. Juan Antonio Samaranch - Collado Martínez, María (Citius, altius, fortius: humanismo, sociedad y deporte: investigaciones y ensayos, 2017)
The objective of this paper is to make a tour of the most important aspects of the life of Dionisio de la Huerta, precursor of tennis in Spain and especially canoeing through The Descent of the River Sella, which has made it to evolve from a source regional competition, to become international, involving several times over 20 countries, a figure that is only achieved in continental, World championships or Olympic Games, since for many years was the most important Spanish sporting event. We will review the characteristics that made it possible through its creator, decorated with the Medal of the Sports Forgers granted by the Generalitat of Catalonia and 3 times with the Medal of Sports Merit, his relationship with Juan Antonio Samaranch, National Delegate of the Movement and President of the International Olympic Committee and we will analyze the elements of the International Descent of the Sella from the perspective of the Greek Olympic Games.